Discourse Markers in Arabic: A Sociopragmatic Perspective on Meaning and Interaction/ علامات الخطاب في اللغة العربية: منظور سوسيوتداولي للمعنى والتفاعل - Lela Haddady; Mende Carlo (IJAS: International Journal of Arabic Studies, 2026)
This study investigates the pragmatic functions of discourse markers in contemporary Arabic from a sociopragmatic perspective, emphasizing their role in meaning construction and interactional organization. While discourse markers have often been examined from structural or textual viewpoints, this research argues that their functions extend beyond cohesion to include social, cognitive, and interactional dimensions. Employing a qualitative exploratory design, the study analyzes naturally occurring data drawn from spoken conversations, media discourse, and digital communication. The findings reveal that Arabic discourse markers such as yaʿnī, ṭayyib, wallāh, and idhān perform multiple overlapping functions, including managing turn-taking, mitigating speech acts, framing arguments, signaling stance, and constructing interpersonal alignment. The analysis further demonstrates that the interpretation of these markers is highly context-dependent and shaped by sociocultural norms, speaker identity, and communicative goals. From a relevance-theoretic and conversation-analytic standpoint, discourse markers function as procedural cues that guide inferential processes and reduce cognitive processing effort. Moreover, their use in digital environments reflects evolving patterns of identity performance and interactional style in contemporary Arabic discourse. The study contributes to Arabic pragmatics by offering an integrative analytical framework that bridges cognitive pragmatics, sociolinguistics, and critical discourse analysis. It also highlights the need for corpus-based and cross-dialectal research to further explore the dynamic role of discourse markers in Arabic communication.